CERIUM(III) CARBONATE HYDROXIDE NANOPARTICLES ENCRUSTED BY METALLIC PALLADIUM. SYNTHESIS AND INVESTIGATION - T. M. Buslaeva; E. V. Kopylova; V. I. Popenko; A. M. Potapova; V. V. Fomichev (Тонкие химические технологии, 2016)
Cerium(III) nitrate and urea solution mixture were treated by hydrothermal and microwavehydrothermal methods, as a result cerium(III) carbonate hydroxide nanoparticles (22-37 nm) were obtained. Cerium(III) carbonate hydroxide nanoparticles, encrusted by palladium were obtained using palladium reduction process from cerium(III) carbonate hydroxide solution. It is shown, that palladium occurrence disturbs hard hydrogen bond system, leading to carbonate hydroxide nanoparticles structure disorder and also increases efficiency of catalytic reactivity process.